Relating Sustainability Metrics to Evaluate Circularity and Material Efficiency - Marshalek, Austin; Zion, Andie; Silverman, Julian R. (Sustainability & Circularity NOW, 2025)
By collecting both green chemistry and environmental impact metrics, researchers can quantitatively discuss the circularity and sustainability of various chemical and material products and processes. Specific extensive quantities from a transformation are related to afford intensive properties for a system, which can be compared across systems. Because different metrics are suited for discussing the diverse aspects of sourcing, transformation, and disposal of reactants, reagents, products, and waste, to meaningfully describe both circularity and sustainability, at least three metrics are needed. Here we compare, contrast, and relate the intensive metrics of recycled content, process mass intensity, and e-factor to describe the renewable content of feedstocks, the efficiency of a process, and the cycling of outputs as input feedstocks. Using data from mass balances, we can calculate these metrics in order to have a simple and concise set of tools that describe both the circularity and material efficiency of a process.
Keywords: sustainability; circularity; material efficiency; metrics; intensive and extensive properties